Citrus tristeza virus-host interactions - Dawson, William O.; Garnsey, Stephen M.; Tatineni, Satyanarayana; Folimonova, Svetlana Y.; Harper, Scott J.; Gowda, S (Frontiers in Microbiology, 2013)
Citrus tristeza virus (CTV) is a phloem-limited virus whose natural host range is restricted to citrus and related species. Although the virus has killed millions of trees, almost destroying whole industries, and continually limits production in many citrus growing areas, most isolates are mild or symptomless in most of their host range. There is little understanding of how the virus causes severe disease in some citrus and none in others. Movement and distribution of CTV differs considerably from that of well-studied viruses of herbaceous plants where movement occurs largely through adjacent cells. In contrast, CTV systemically infects plants mainly by long-distance movement with only limited cell-to-cell movement. The virus is transported through sieve elements and occasionally enters an adjacent companion or phloem parenchyma cell where virus replication occurs. In some plants this is followed by cell-to-cell movement into only a small cluster of adjacent cells, while in others there is no cell-to-cell movement. Different proportions of cells adjacent to sieve elements become infected in different plant species. This appears to be related to how well viral gene products interact with specific hosts. CTV has three genes that are not necessary for infection of most of its hosts, but are needed in different combinations for infection of certain citrus species. These genes apparently were acquired by the virus to extend its host range. Some specific viral gene products have been implicated in symptom induction. Remarkably, the deletion of these genes from the virus genome can induce large increases in stem pitting symptoms. The p23 gene, which is a suppressor of RNA silencing and a regulator of viral RNA synthesis, has been shown to be the cause of seedling yellows symptoms in sour orange. Most isolates of CTV in nature are populations of different strains of CTV. The next frontier of CTV biology is the understanding how the virus variants in those mixtu